Pitfalls encountered while projecting the future Israeli anesthesiologist workforce: lessons from the Israel anesthesiologist workforce study - Ariel Wimpfheimer; Yehuda Ginosar; Daniela Quesada; Shai Fein; Charles Weissman; Haled Abd-Al-Halim; Hakeem Abu-Rais; Chaim Berkenstadt; Ilya Chernoy; Maruan Armaly; Yaakov Duvdivani; Leonid Eidelman; et al. (Israel Journal of Health Policy Research, 2026)
Abstract Background The smooth and efficient operation of a country’s healthcare system is highly dependent on the size and specialty composition of its physician workforce. Therefore, it is incumbent upon a country’s healthcare leadership to continually examine the workforce situation in each medical specialty, especially critical specialties like anesthesiology, so as to detect issues that could lead to shortfalls and surpluses and then apply effective corrective actions. The aim was to assess the accuracy of the different predictive methods and identify possible ways of improving their predictive capabilities. Our assumption was that the accuracy of workforce predictions is primarily affected by unforeseen and disruptive events. Methods Cross-sectional surveys of the Israeli anesthesiology workforce were performed in 2005 ( n = 711 anesthesiologists) and 2021 ( n = 1330 anesthesiologists). This permitted comparing needs and demand-based workforce forecasts made in 2005 with the actual 2021 workforce. Reasons for discrepancies between the 2005 forecasts and the reality in 2021 were sought. Results The 2005 needs-based projections underestimated the actual increase in anesthesiologists because the population grew at a rate faster than that estimated in 2005. Furthermore, there was an increase in the proportion of the population > 65 years old, an increase in life expectancy and a higher birth rate requiring a greater number of caesarean sections and epidural catheter insertions. Moreover, the 2011 union contract between the government and the Israel Medical Association increased anesthesiologist vacation time by two weeks per year. The demand-based projection underestimations were attributed to the significant increase in anesthetics performed outside operating rooms, such as, in cardiac catheterization laboratories and invasive radiology and endoscopy suites. Comparing anesthesiologist workforce projections made in 2005 to the workforce realities 16 years later revealed that many unpredictable (greater population growth) and disruptive (union contract) factors that ensued during that time period led to underestimating future workforce needs. Conclusions Forecasting the future Israeli physician anesthesiologist workforce is an endeavor fraught with unpredictable challenges. To facilitate frequently updated forecasts of future workforce needs, healthcare systems require robust, long-term forecasting capabilities that use near real-time data obtained from the ubiquitous electronic medical and hospital record systems. These data should then be entered into sophisticated data analytic tools, rather than simple needs and demand-based methods. Such up-to-date forecasts should help healthcare system leaders and policy makers make more informed workforce decisions.